Semasiology: Exploring the Meanings of Words ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2023)
Semasiology is a linguistic branch that examines how words acquire and change meanings within a language. This article explores the subject matter of semasiology and highlights its relevance in understanding language and effective communication. Semasiology is a branch of linguistics that delves into the study of meanings and the changes they undergo within a language. This fascinating field focuses on the various ways in which words acquire and evolve their meanings. This article provides an overview of semasiology, its subject matter, and the importance of studying word meanings in understanding language and communication.